Dermatology eponyms - sign - Lexicon (R): Part 2 - Piotr Brzeziński; Max Carlos Ramírez Soto; Patrice Bourée; Balachandra S. Ankad; Shirish Dubey; Shivanand Gundalli; Martin G. Baartmans; Tomasz Wasyłyszyn; Katarzyna Borowska; Anca Chiriac (Our Dermatology Online, 2017)
Eponyms are used almost daily in the clinical practice of dermatology. And yet, information about the person behind the eponyms is difficult to find. Indeed, who is? What is this person's nationality? Is this person alive or dead? How can one find the paper in which this person first described the disease? Eponyms are used to describe not only disease, but also clinical signs, surgical procedures, staining techniques, pharmacological formulations, and even pieces of equipment. In this article we present the symptoms starting with (R) and other. The symptoms and their synonyms, and those who have described this symptom or phenomenon.